Developing agri-based technopreneurs in the academe the case of two DOST-funded projects in the University of the Philippines Los Baños - Depositario, Dinah Pura T.; Panabang, Maritess B.; Zapata, Normito R. Jr.; Aquino, Nanette A.; Abarquez, Laida J. (2011)
This paper assesses the outcome of two Department of Science and Technology (DOST)-funded projects geared towards promoting technopreneurship among students of the University of the Philippines Los Baños (UPLB). It describes the various technopreneurial trainings and other inputs under the Agriculture. Forestry, and Natural Resources (AFNR) project. Then, using an action research design, it documents and examines the experiences of twenty-six (26) student-technopreneurs who conducted start-up businesses for five months using three UPLB-developed technologies, with supplementary funds coming from the Philippine Council for Industry, Energy, and Emerging Technology Research and Development (PCIEERD-DOST). The study uses primary and secondary data from the student-technopreneurs, validated through key informant interviews, to gain insights into the process of running the start-ups, including the challenges encountered and lessons learned, and then evaluates their performance using three parameters, namely, financial performance, entrepreneurial competencies developed, and the number of businesses registered after the project. Results show that the student-technopreneurs under the high-end cheese and by-products track were the most financially successful, followed by those under the fruit juice and puree track. Those under the microbial rennet were the least successful. All of the participants reportedly gained personal entrepreneurial competencies, the most important of which being acquisition of technological know-how. On the overall, the two projects are assessed to be successful. Lastly, only seven registered their businesses as most perceived that their current production scale was too small to require business registration. The paper then provides future directions for research and recommendations on how to improve the conduct of similar projects based on the experiences of the participants and the insights from the project management team.
Keywords: Agri-based technopreneurs; Student-technopreneurs; Technopreneurship